Assessing Indonesian Consumer Adoption of Digital Banking Using the Extended UTAUT2 Model - Pranoto, Bagus Unggul; Aprilianty, Fitri (Journal of Business and Management, 2020)
Abstract. The ideal conditions of Indonesia’s market such as the high number of smartphone users and digital penetration in Indonesia have become cues for bank service providers to develop digital banking technology for their clients. Despite the positive response to the digital shift, the adoption of digital banking is still relatively low compared to the potential high numbers of smartphone users. This study intends to gain a deeper understanding on the factors affecting people’s intention to adopt and use behavior of digital banking application in Indonesia as well as fill in the gap found in previous studies by using an extended UTAUT2 model. This study includes factors outside UTAUT2 modelsuch as Trust, Perceived Self-Efficacy, and Firm Reputation found in previous studies and Digital Banking User Experience as a newly added factor to differentiate this study from mobile banking studies. Through online survey method, this study gathered data from 323 digital banking adopters. The SEM-PLS analysis indicates that all of the data are valid and reliable. Moreover, the result shows that Performance Expectancy, Facilitating Condition, Hedonic Motivation, Price Value, and Habit were found to have a significant impact on Behavioral Intention to adopt digital banking. In addition, Habit was also found to have a significant impact on the use behavior of digital banking. Furthermore, this study gives digital banking providers insights based on their consumers which could help them understand the factors that drives users to adopt digital banking and increase the adoption rate of digital banking in Indonesia. This study also contributes to the development of UTAUT2 theory to be used in the context of digital banking adoption.Keywords: Behavioral Intention, Consumer Adoption, Digital Banking, SEM-PLS, UTAUT2